Four-point bending tests for the fracture properties of concrete. (15th April 2019) - Yin, Yangyang; Qiao, Yanmin; Hu, Shaowei
Highlights: The fracture properties of concrete were evaluated using four-point bending notched beams. The effect of initial crack-depth ratio on fracture parameters was revealed. Specimens with initial crack-depth ratios of 0.2 and 0.3 show more brittle behavior. K IC values determined by the provided two approaches were almost identical. A constant G F was obtained based on work-of-force. Abstract: This paper evaluates the fracture properties of concrete using four-point bending test which the beam segment near the midspan crack section is under pure bending. Five different initial crack-depth ratios varying from 0.2 to 0.6 for concrete specimens were explored. The corresponding values of load, crack mouth opening displacement and midspan deflection were simultaneously recorded. The fundamental fracture parameters of critical effective crack extension length, critical effective fracture toughness and fracture energy were analyzed. More specifically, two approaches named pure bending approach and FPB approach were introduced to determine the critical effective fracture toughness. The results indicate that four-point bending test can be utilized to study the fracture properties of concrete.